Improving Student’s Vocabulary Mastery Through Memorizing Multi Senses Technique - Riki Agustiono; Syamsul Rizal; Nadrah (Jadila: Journal of Development and Innovation in Language and Literature Education)
The results of this study showed that the experimental group applying memorizing multi Senses techniques in teaching and learning, students scored better than the control group were not applying the technique of memorizing multi senses in the classroom. In the experimental group, the highest score was 90 and the lowest score was 60. While in the control group was the highest score was 75 and the lowest score was 35.Achievement students from both groups have different achievements. After passing the pre-test, treatment, and post-test, the students in the experimental group had improved its score high, fixed in the control group, student achievement scores in the mastery of vocabulary is still low. It is indicating that there are significant differences in the achievement of vocabulary achieved by students who have been using memorizing multi senses technique.